In Stent Restenosis Predictors after Carotid Artery Stenting - Mirco Cosottini; Maria Chiara Michelassi; Walter Bencivelli; Guido Lazzarotti; Silvia Picchietti; Giovanni Orlandi; Giuliano Parenti; Michele Puglioli (Stroke Research and Treatment)
Purpose. The long-term efficacy of carotid artery stenting is debated. Predictors of stent restenosis are not fully investigated. Our aim was to assess the incidence of long term restenosis after CAS and to identify some predictors of restenosis. Methods. We retrospectively selected 189 treated patients and we obtained the survival Kaplan-Meier curves for overall survival, for freedom from stroke or death and from restenosis. To correlate clinical, radiological, and procedural variables to stent restenosis, an univariate analysis was performed while to determine independent predictors of restenosis, a multivariate analysis was applied. Results. At 1, 3, and 5 years, the cumulative overall survival rate was 98%, 94%, and 92% with a cumulative primary patency rate of 87%, 82.5%, and 82.5%. The percentage residual stenosis after CAS and multiple stents deployment were independent predictors of restenosis, while diabetes and tumors are suggestive but not significant predictors of restenosis. Conclusions. In our CAS experience, encouraging long-term results seem to derive from both neurological event free rate and restenosis incidence. Adequate recanalization of the treated vessel is important to limit the development of stent restenosis. Multiple stents deployment, and with less evidence, diabetes, or neoplasms has to be considered to facilitate restenosis.